Aortic Rupture during Endovascular Repair of a Postoperative Coarctation Pseudoaneurysm in an Adult: Emergency Lifesaving Stent Graft Implantation - Kratimenos, Theodoros (Ann Card Anaesth, 2019)
We present a case with aortic rupture during an operation of thoracic endovascular aortic repair of an anastomotic pseudoaneurysm. This happened after the use of a low-pressure remodeling balloon inside the covered part of the deployed endografts. It was successfully treated with a second more centrally in the aortic arch-implanted endograft with full coverage of the left subclavian artery orifice. This patient had a history of surgically operated aortic coarctation.